Analisis Brand Equity Perguruan Tinggi Swasta di Bandar Lampung - Aswin Aswin; Cahyani Pratisti; Muhammad Saputra (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2021)
Business competition among education services in Bandar Lampung is rapidly raising, including private universities. Brand equity is proven to increase the universities profitability in the long term. This qualitative research aims to provide a comparison of the brand equity among private universities in Bandar Lampung. Through descriptive analysis and cochran q-test from 560 combined informants from high school and collegues found that in high school IIB Darmajaya was Top of mind IIB Darmajaya, Recall brand was Technocrats University, and Brand recognition that they knew IIB Darmajaya from friends and family. Whereas the collegues obtained Top of mind was IIB Darmajaya, Brand recall IIB Darmajaya was identical to Computer Science and Economics, Brand recognition recognizes IIB Darmajaya from logos, slogans and taglines, Brand association that IIB Darmajaya had a good image, good quality private campus, an innovative campus, had a variety of student activities, and Brand loyalty in good categories also. Promotional activities both directly and digitally to high school students absolutely needed to improve IIB Darmajaya's brand recall. Abstrak Persaingan bisnis antar jasa pendidikan di Bandar Lampung semakin pesat, tak terkecuali perguruan tinggi swasta. Ekuitas merek dalam jangka panjang terbukti dapat meningkatkan profitabilitas perguruan tinggi. Penelitian kualitatif ini bertujuan untuk memberikan perbandingan ekuitas merek perguruan tinggi swasta di Bandar Lampung. Melalui analisis deskriptif dan uji cochran q-test dari informan siswa/i SMA/sederajat sebanyak 250 orang dan mahasiswa/i 410 mahasiswa, didapat bahwa pada siswa/i SMA/sederajat Top of mind Perguruan Tinggi Swasta adalah IIB Darmajaya, Brand recall Universitas Teknokrat, dan Brand recognition mengetahui merek Darmajaya dari teman dan keluarga. Sedangkan pada mahasiswa/i didapat Top of Mind Perguruan Tinggi Swasta adalah IIB Darmajaya, Brand recall IIB Darmajaya identik dengan ilmu komputer dan ilmu ekonomi, Brand recognition mengenali IIB Darmajaya dari logo, serta slogan dan tagline, dan Brand association IIB Darmajaya memiliki citra yang baik, kampus swasta yang bermutu, kampus yang inovatif, memiliki ragam kegiatan mahasiswa, serta Brand loyalty dalam kategori baik. Kegiatan promosi baik secara langsung maupun digital kepada siswa/i SMA diperlukan untuk meningkatkan brand recall IIB Darmajaya.